The crisis of local leadership: a passing trend or a systemic problem? - Klačar, Bojan (Serbian political thought, 2023)
In this paper, the author will examine the influence of the electoral system at the local level and the party system with a hegemonic or (pre)dominant party on the development of local political leadership. The main point is that Serbia is going through a crisis in the development of local leadership (and local democracy) as a consequence of centralization of political decisions and merging local elections with national ones, as well as a PR electoral system with one electoral unit. This kind of electoral system, according to its inherent characteristics, produces a lack of communication between the elected representatives and the electorate, thereby losing an important step necessary in building leadership. The author analyses how the combination of high centralization in decision-making process and weak internal democracy within political parties and the electoral system in the long term encourages the negative selection of political elites at the local level. A logic incentive for local leaders and local democratic processes is to increase their political rating by communicating with voters. In practice, the reverse process takes place at the local level: politicians understand that their rating depends less on electorate and more on intra-party practices, and in Serbia, they are overwhelmingly of an undemocratic nature. The author will analyse the party leadership of the relevant political parties/organizations in Serbia, internal party elections and the mobility of local leaders in the party hierarchy. Through secondary sources and document analysis, the derogation of local leadership and democracy and their exchange (trade off) for the stability of political processes at the national level are analysed. Also, 15 case studies of successful local leaders after 2004 and the outcomes of their political careers are discussed.
Keywords: local elections, local lidership, electoral system, political party, voters